2020
DOI: 10.1136/rmdopen-2020-001321
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s experience of psoriatic arthritis: a conceptual model based on qualitative interviews

Abstract: IntroductionPsoriatic arthritis (PsA) is a heterogeneous chronic inflammatory musculoskeletal disorder that manifests as peripheral arthritis, dactylitis, enthesitis and spondylitis. PsA results in significant burden that impacts quality of life of patients. We examined the signs, symptoms and impacts reported by patients with PsA, to characterise the patient experience of PsA and develop a conceptual model representing this patient experience.MethodsSemi-structured interviews were conducted with patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…This study found that symptoms related to musculoskeletal pain were the most bothersome symptoms of PsA, compared with psoriasis-related symptoms, in rheumatology-focused patients with overall low skin disease severity. This finding mirrors other patient impact studies in PsA [3,16,28,29], and patients and rheumatologists are generally in agreement that joint pain is the most burdensome symptom of PsA [30]. However, our findings also highlight other interesting trends.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that symptoms related to musculoskeletal pain were the most bothersome symptoms of PsA, compared with psoriasis-related symptoms, in rheumatology-focused patients with overall low skin disease severity. This finding mirrors other patient impact studies in PsA [3,16,28,29], and patients and rheumatologists are generally in agreement that joint pain is the most burdensome symptom of PsA [30]. However, our findings also highlight other interesting trends.…”
Section: Discussionsupporting
confidence: 90%
“…Pooled analysis of the DISCOVER trials found resolution of enthesitis by 45–50% of the guselkumab group compared with 29% of placebo and resolution of dactylitis by 59–64% of the guselkumab group compared with 42% of placebo; baseline scores were also significantly decreased after 24 weeks of treatment [ 69 ]. Similar efficacy in dactylitis and enthesitis was seen through 56 weeks in a phase II trial of patients with active PsA despite current or previous conventional therapy [ 70 ].…”
Section: Treatment Of Psoriatic Arthritismentioning
confidence: 69%
“…PROs reflect many important issues that significantly impact patients with PsA, including challenges in mental, physical, and social functioning, pain, fatigue, work-related disability, in addition to psoriatic, axial, and skin disease symptoms. Many of these symptoms and sequelae of disease are represented by the core domains recommended by the GRAPPA-OMERACT working group to be measured in all RCTs to evaluate treatment efficacy [2,3,18,[37][38][39][40]. In a recent qualitative interview study of PsA patients recruited through the FORWARD databank, joint pain and stiffness, skin symptoms, fatigue, and physical disability were identified as some of the most salient PsA symptoms [39].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these symptoms and sequelae of disease are represented by the core domains recommended by the GRAPPA-OMERACT working group to be measured in all RCTs to evaluate treatment efficacy [2,3,18,[37][38][39][40]. In a recent qualitative interview study of PsA patients recruited through the FORWARD databank, joint pain and stiffness, skin symptoms, fatigue, and physical disability were identified as some of the most salient PsA symptoms [39]. Similarly, pain, fatigue, and poor HRQOL have been identified as some of the highest-ranking outcomes that patients would want treatment to remedy [40].…”
Section: Discussionmentioning
confidence: 99%